The Effect of a Training Program on Improving Motor Response and some Basic Skills of Junior Table Tennis Players: Pengaruh program pelatihan terhadap peningkatan respons motorik dan beberapa keterampilan dasar pemain tenis meja pemula - Bishara, Dr. Kazem Jakhior (Indonesian Journal of Education Methods Development, 2026)
General Background: Scientific training programs play a fundamental role in developing motor and technical abilities in youth sports. Specific Background: In table tennis, rapid motor response and precise execution of forehand and backhand strokes are essential for competitive performance, yet junior players often demonstrate weaknesses due to limited specialized training and insufficient use of modern response-speed devices. Knowledge Gap: There is limited structured application of neuromuscular-based training curricula incorporating electronic response-speed devices within junior table tennis development programs. Aims: This study examined a proposed eight-week training program designed to develop motor response speed and selected basic skills among six junior table tennis players in Najaf Governorate. Results: Pre- and post-test comparisons revealed statistically significant improvements in motor response speed measured using the BATAK MICRO device, alongside significant gains in forehand and backhand technical performance scores. The experimental group outperformed the control group across all measured variables. Novelty: The program integrated device-based response training with progressive, match-simulated technical drills tailored to junior developmental characteristics. Implications: The findings support incorporating structured neuromuscular exercises and stimulus-based drills into youth training curricula to improve response time, coordination, and technical precision in table tennis development programs. Keywords: Motor Response Speed, Junior Table Tennis, Training Program, Neuromuscular Coordination, Technical Performance Key Findings Highlights: Significant gains in reaction metrics were recorded after eight weeks of structured practice. Forehand execution accuracy showed marked statistical progression. Backhand stroke consistency improved through progressive stimulus-based drills.